The Influence of Liabilities and Profitability on the Value of GIAA Companies Listed on the Indonesia Stock Exchange 2023-2024 - Noval Alvian Nugraha; Adi Saputra; Helmy Aprichila Dinova; Eteh Resa Asyifa (Sean Institute, 2026)
This study aims to examine and analyze the effect of liabilities and profitability on the firm value of PT Garuda Indonesia (Persero) Tbk (GIAA), which is listed on the Indonesia Stock Exchange. Firm value represents an important indicator that reflects investors’ perceptions of the company’s performance as well as its future prospects. In the aviation industry, which is characterized by high capital requirements and intense competition, understanding the factors that influence firm value is crucial for management and other stakeholders.The independent variables in this study consist of liabilities measured using the Debt to Equity Ratio (DER), and profitability measured through Return on Equity (ROE) and Return on Assets (ROA). Meanwhile, the dependent variable is firm value, which is measured using Price to Book Value (PBV) and Tobin’s Q. The data used in this research are secondary data in the form of financial statements of PT Garuda Indonesia (Persero) Tbk for the 2021–2024 period, obtained from the Indonesia Stock Exchange and the company’s official website.